Functional disruption of stress modulatory circuits in a model of temporal lobe epilepsy. - Aynara C Wulsin; Ana Franco-Villanueva; Christian Romancheck; Rachel L Morano; Brittany L Smith; Benjamin A Packard; Steve C Danzer; James P Herman (PLoS ONE)
Clinical data suggest that the neuroendocrine stress response is chronically dysregulated in a subset of patients with temporal lobe epilepsy (TLE), potentially contributing to both disease progression and the development of psychiatric comorbidities such as anxiety and depression. Whether neuroendocrine dysregulation and psychiatric comorbidities reflect direct effects of epilepsy-related pathologies, or secondary effects of disease burden particular to humans with epilepsy (i.e. social estrangement, employment changes) is not clear. Animal models provide an opportunity to dissociate these factors. Therefore, we queried whether epileptic mice would reproduce neuroendocrine and behavioral changes associated with human epilepsy. Male FVB mice were exposed to pilocarpine to induce status epilepticus (SE) and the subsequent development of spontaneous recurrent seizures. Morning baseline corticosterone levels were elevated in pilocarpine treated mice at 1, 7 and 10 weeks post-SE relative to controls. Similarly, epileptic mice had increased adrenal weight when compared to control mice. Exposure to acute restraint stress resulted in hypersecretion of corticosterone 30 min after the onset of the challenge. Anatomical analyses revealed reduced Fos expression in infralimbic and prelimbic prefrontal cortex, ventral subiculum and basal amygdala following restraint. No differences in Fos immunoreactivity were found in the paraventricular nucleus of the hypothalamus, hippocampal subfields or central amygdala. In order to assess emotional behavior, a second cohort of mice underwent a battery of behavioral tests, including sucrose preference, open field, elevated plus maze, 24h home-cage monitoring and forced swim. Epileptic mice showed increased anhedonic behavior, hyperactivity and anxiety-like behaviors. Together these data demonstrate that epileptic mice develop HPA axis hyperactivity and exhibit behavioral dysfunction. Endocrine and behavioral changes are associated with impaired recruitment of forebrain circuits regulating stress inhibition and emotional reactivity. Loss of forebrain control may underlie pronounced endocrine dysfunction and comorbid psychopathologies seen in temporal lobe epilepsy.